Content development experience of a start-up university. (1st January 2011) - Zain, Zuraidah Mohd; Shukor, Nasrudin Abdul
In this paper we describe our experience in implementing an e-learning content development project at a Malaysian start-up engineering university. Given the teaching-learning culture and resources at the time the project started, certain decisions were made. Outside help, in the form of a consultant company that provided the services of instructional designers, graphic designers, content animation developers, and learning management system (LMS) integrators was procured. In the course of the project, several painful but useful lessons were learned. Lack of time on the part of the subject matter experts (SMEs), aggravated by some basic pedagogical-related differences between the instructional designers and the SMEs when designing and developing storyboards, resulted in a delay of the project's completion. After having gone through the experience, the university has decided that in future, e-learning would be pursued with a slightly different emphasis, whereby content development would be given secondary precedence, while full deployment of available LMS features, utilising off-the-shelf e-modules, be given priority.